2020
DOI: 10.1002/jmv.26180
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features and viral shedding in children with SARS‐CoV‐2 infection

Abstract: A pandemic of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection broke out all over the world; however, epidemiological data and viral shedding in pediatric patients are limited. We conducted a retrospective, Chun-Zhen Hua and Zi-Ping Miao contributed equally to this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 25 publications
1
105
0
Order By: Relevance
“…Additionally, 71.2% (52/73) were still positive for fecal nucleic acid after the respiratory tract specimens turned negative, 45.2% (33/73) were fecal nucleic acid-positive one week after the respiratory tract specimen was nucleic acid-negative, and 34.2% (25/73) were fecal nucleic acid-positive two weeks after a respiratory tract nucleic acid negative test. A study from Anhui Province in China found that the longest interval between the respiratory tract specimen turning negative and fecal specimen turning negative exceeded 70 days 34 . However, in a study on three neonates 27 , respiratory tract and fecal nucleic acid tests were positive 2 and 4 days after birth, respectively, and the fecal and respiratory tract specimens were negative on the 6th day after birth.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 71.2% (52/73) were still positive for fecal nucleic acid after the respiratory tract specimens turned negative, 45.2% (33/73) were fecal nucleic acid-positive one week after the respiratory tract specimen was nucleic acid-negative, and 34.2% (25/73) were fecal nucleic acid-positive two weeks after a respiratory tract nucleic acid negative test. A study from Anhui Province in China found that the longest interval between the respiratory tract specimen turning negative and fecal specimen turning negative exceeded 70 days 34 . However, in a study on three neonates 27 , respiratory tract and fecal nucleic acid tests were positive 2 and 4 days after birth, respectively, and the fecal and respiratory tract specimens were negative on the 6th day after birth.…”
Section: Resultsmentioning
confidence: 99%
“…The coronavirus disease-19 (COVID-19) pandemic is an ongoing world crisis. This pandemic has taken a toll on human health and has also placed a huge burden on economies, societies, and families across the globe (Carter et al, 2020;Cutler, 2020;Donthu and Gustafsson, 2020;Hua et al, 2020;Jenson, 2020;Mclaren et al, 2020;Ornell et al, 2020;Power, 2020;Satiani et al, 2020). This COVID-19 crisis is further deepened because the future of countries, societies, and individuals is uncertain and unpredictable in the months and perhaps years to come.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from December 2019, a novel coronavirus (SARS-CoV-2), causing coronavirus disease 2019 (COVID-19), has spread on a global scale [ 1 ]. Compared to adults, children seem to be less affected by SARS-CoV-2 infection as they are usually asymptomatic or have mild symptoms [ [1] , [2] , [3] , [4] ]. However, little is known about disease severity in neonates, the need for treatment and their role in transmission of SARS-CoV-2 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in children aged between 2 months and 15 years, SARS-CoV-2 RNA could still be detected in their stool in up to 70 days [ 4 , 8 , 9 ]. Data about duration of viral shedding in neonates is scarce [ 10 , 24 , 27 , 33 ].…”
Section: Introductionmentioning
confidence: 99%